Influencing cardio-pulmonary resuscitation intentions in Singapore : an examination of the effects of message appeals on protection motivation theory. - Chia, Kenneth Mu Mao. (2009)
Cardiopulmonary resuscitation (CPR) is crucial for survival during sudden cardiac arrest (Hopstock, 2007), the most frequent cause of death resulting from coronary heart diseases. Figures from different countries have shown that the typical low survival rate of pre-hospital cardiac arrest victims can increase manifold when the public is CPR-trained. CPR education programmes have been available in Singapore since 1983, but to date, only 20% of out-of-hospital cardiac arrests (OHCA) receive bystander CPR (Lateef & Anantharaman, 2001). This research examines the intention to learn cardio-pulmonary resuscitation (CPR) amongst youths in Singapore. A survey was first used to examine the predictive utility of Protection Motivation Theory (PMT) for CPR intention among 359 youths. Findings revealed that coping-appraisal components of PMT (namely perceived self-efficacy and perceived response-efficacy) were useful in predicting CPR intentions. We then conduct an experiment with 426 participants to examine the effects of message appeals on intentions to learn CPR. The experimental results show that fear priming enhances the effects of guilt message appeal, which leads to higher coping appraisals and behavioral intention. We discuss the implications for health agencies and social marketers.